Formalina y sal común contra la infestación de monogenóideos branquiales (Monogenoidea: Dactylogyridae) en juveniles de paiche Arapaima gigas provenientes de estanques de cultivo de la carretera Iquitos - Nauta, Loreto - Perú - Mora Del Águila, Hugo Adín (2022)
Monogenoids are parasites responsible for most of the economic losses in fish farming. It is important to know the effective mechanisms or products to control this group of parasites. Although formalin and salt are frequently used in the treatment of fish diseases, specific studies are necessary in order to verify which concentrations are more effective and less harmful to the health of the species to be treated. Thus, the present study tested the efficacy of salt and formalin against monogenoid infestations in specimens of A. gigas collected from producers on the Iquitos-Nauta highway. The collected fish were transferred to the Parasitology and Aquaculture Health laboratory of the Fernando Alcántara Bocanegra Research Center of the Peruvian Amazon Research Institute. In the laboratory, in situ and in vitro treatments were carried out to determine the efficacy of the products. The treatments used were: salt at a rate of 15, 25 and 30g / L and formalin at a rate of 0.2, 0.3 and 0.4 ml / L. The species identified parasitizing the gills of A. gigas was Dawestrema cycloancistrium. In the in vitro treatments all the treatments were effective in killing the parasites. The time of action was shorter as the dose was increasing. In the in situ treatments, the efficacy of the products was also demonstrated, causing "zero" mortalities. As the doses of the products were increased, they were more effective. Among the treatments used, salt at a rate of 30g / L almost completely eliminated the monogenoids that infested the gills of the A. gigas specimens used. Salt and formalin are effective products for the control of branchial monogenoids in cultured A. gigas.